TRANSPOSITION OF EU ENVIRONMENTAL LEGISLATION FOR PROTECTING WATERS IN BULGARIA: TRANSPOSITION OF EU ENVIRONMENTAL LEGISLATION FOR PROTECTING WATERS IN BULGARIA - Zheleva, Ivanka; Filipova, Margarita; Roussev, Petar; Rayanova, Kremena (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The chronology and the extent to which Republic of Bulgaria laws in the water protection field correspond to EU legislation is presented in the paper. The key issues and opportunities for prevention, quality control and river waters protection from different types of contaminants are analyzed.